Nanotechnology and Neuroscience: Nano-electronic, Photonic and Mechanical Neuronal Interfacing - De Vittorio, Massimo; Martiradonna, Luigi; Assad, John (Springer New York : Imprint: Springer, 2014)
This book provides an overview of the different ways in which the "nano-world" can be beneficial for neuroscientists. The volume encompasses the latest developments in the field of micro- and nanotechnology applied to neuroscience, discussing technological approaches applied to both in-vitro and in-vivo experiments. A variety of different nanotechnologies are presented that include nanostructured electrodes and their electrical, mechanical and biochemical properties, active and passive 2D and 3D multi-electrode arrays (MEAs), nanoscale transistors for sub-cellular re-cordings and an overview on methods, tools and applications in optoge-netics. The book focuses specifically on fabrication strategies, to offer a compre-hensive guide for developing and applying micro- and nanostructured tools for neuroscientific applications. It is intended as a reference both for neuroscientists and nanotechnologists on the latest developments in neu-rotechnological tools.   • Provides readers with state-of-the-art information about developing advanced nanotechnology tools for communicating with the brain; • Includes discussion of the compatibility of fabrication techniques optimized for different target devices, such as electric sensors/transducers based on metallic or semiconductor interfaces and optical probes to guide light into the brain; • Offers a single-source reference to the mechanical, electrical and optical effects of nanostructures on neurons.        .